Nanostructured Solar Cells - Das, Narottam (InTechOpen, 2017)
Nanostructured solar cells are very important in renewable energy sector as well as in environmental aspects, because it is environment friendly. The nano-grating structures (such as triangular or conical shaped) have a gradual change in refractive index which acts as a multilayer antireflective coating that is leading to reduced light reflection losses over broadband ranges of wavelength and angl...